Cooperative binding by a bifunctional deoxycholic acid and cocaine-binding aptamer. (2021) - Dawood, Nusaibah E; Slavkovic, Sladjana; Qureshi, Ruqaiya; Khamissi, Natalie; Bauer, Christina; Reinstein, Oren; Johnson, Philip E
No abstract available